2017
DOI: 10.1108/dpm-05-2016-0101
|View full text |Cite
|
Sign up to set email alerts
|

Flood vulnerability and relocation readiness in Zimbabwe

Abstract: Purpose The purpose of this paper is to examine vulnerability conditions to flood disasters in Tokwe-Mukorsi community, Zimbabwe and identifies the barriers that constrained the community from relocating to safe sites. Design/methodology/approach Using a questionnaire survey, field observations and interviews, the paper examines the biophysical and social vulnerability of the Tokwe-Mukorsi community, Zimbabwe, as well as the barriers that prevented it from relocating to safe sites. A thematic analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Likewise, critical situations, while they can be stressful and difficult to manage for some affected people, can also empower processes and skills for other participants in the community context, generating responses such as strengthening social organizations, increasing organizational capacity and community preparedness to deal with environmental disasters ( Mavhura et al, 2017 ). In addition, community participation is energized, which in turn increases cohesion and the bonding type of SC that can be observed to some extent in these results.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, critical situations, while they can be stressful and difficult to manage for some affected people, can also empower processes and skills for other participants in the community context, generating responses such as strengthening social organizations, increasing organizational capacity and community preparedness to deal with environmental disasters ( Mavhura et al, 2017 ). In addition, community participation is energized, which in turn increases cohesion and the bonding type of SC that can be observed to some extent in these results.…”
Section: Discussionmentioning
confidence: 99%
“…South America (5%) [37][38][39][40][41] and Africa (4%) [42][43][44][45][46] showed less research interest (Figure 2). Following a detailed analysis of each region, we found that the most researched areas were: the United States, representing 13.19% of the total articles analyzed and 71.72% of the articles located in North America [47][48][49]; the United Kingdom, with 90 articles representing 17.92% of the articles in Europe and 6.78% of the total papers [50][51][52]; Italy and Spain, accounting for 5.27% of the entire articles and 13.94% of the scientific papers published in Europe, respectively [53][54][55]; and China, accounting for 5.27% of the total articles and 20.11% of the articles in Asia [56][57][58]. A significant percentage of publications also came from India, representing 16.6% of all Asian scientific articles and 4.37% of the total publications [59][60][61].…”
Section: Spatial Distribution Of Researchmentioning
confidence: 99%
“…Another important aspect of disaster adversity is the mass scale relocation of the populace and its management from the vulnerable locations to safeguard their interests. This is examined by studies of Mavhura, Collins, and Bongo () involving flood effects on the Tokwe‐Mukorsi community in Zimbabwe and Chen, Tan, and Luo () inspecting the Wenchuan earthquake. Nath et al () divide the disaster mitigation strategies for affected communities into two parts: first, a pre‐disaster strategy of moving the population for flood relief and second, the provision of emergency response services.…”
Section: Literature Reviewmentioning
confidence: 99%